Priority Factors in The Development of Sustainable Oyster Mushroom Agribusiness - Kusrini, Novira; Sulistiawati, Rini; Imelda, Imelda (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Determining factors in the development of sustainable oyster mushroom agribusiness is an important issue presently considering oyster mushrooms have good opportunities and potential. This research aims to identify prioritizing factors in the development of sustainable oyster mushroom agribusiness in Kubu Raya Regency West Kalimantan Province. This research uses the descriptive method. Respondents were 30 key informants from related agencies (Agriculture Office of Food Crops and Horticulture, agricultural extension workers, researchers in horticulture, oyster mushroom entrepreneurs, and oyster mushroom traders). The research was conducted from March to June 2018. Data were analyzed by the Analytical Hierarchy Process (AHP) analysis. The result indicates that supporting facilities aspect is the most important criterion to be considered. The main sub-criteria are oil palm empty fruit bunches (OPEFB) potential (ecology), return on investment (financial), perception and attitudes of the community in consuming oyster mushrooms (socio-culture), capital (institution), labor availability (human resources), adoption readiness (technology), and market (supporting facilities). The main sub-sub criterion is market demand.